Revealing bacterial cell biology using cryo-electron tomography. (August 2022) - Khanna, Kanika; Villa, Elizabeth
Abstract: Visualizing macromolecules inside bacteria at a high spatial resolution has remained a challenge owing to their small size and limited resolution of optical microscopy techniques. Recent advances in cryo-electron tomography (cryo-ET) imaging methods have revealed the spatial and temporal assemblies of many macromolecules involved in different cellular processes in bacteria at a resolution of a few nanometers in their native milieu. Specifically, the application of cryo-focused ion beam (cryo-FIB) milling to thin bacterial specimens makes them amenable for high-resolution cryo-ET data collection. In this review, we highlight recent research in three emerging areas of bacterial cell biology that have benefited from the cryo-FIB-ET technology - cytoskeletal filament assembly, intracellular organelles, and multicellularity. Graphical abstract: Application of cryo-focused ion beam milling coupled to cryo-electron tomography for bacterial cell biology. The review specifically focuses on recent studies in cytoskeletal filaments, intracellular organelles, and bacterial multicellularity. Created with https://biorender.com/ BioRender.com . Made with Biorender.com Image 1 Highlights: Cryo-focused ion beam milling enables sample thinning to image macromolecules in situ using cryo-electron tomography. Cryo-FIB-ET bridges the gap between bacterial cell biology and structural biology. Cryo-FIB-ET has unveiled bacterial structures like cytoskeletal filaments, intracellular compartments, and septal junctions.